2004
DOI: 10.1111/j.1532-5415.2004.52452.x
|View full text |Cite
|
Sign up to set email alerts
|

The Maryland Assisted Living Study: Prevalence, Recognition, and Treatment of Dementia and Other Psychiatric Disorders in the Assisted Living Population of Central Maryland

Abstract: Dementia and psychiatric disorders are common in AL and have suboptimal rates of recognition and treatment. This may contribute to morbidity and interfere with the ability of residents to age in place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
133
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 27 publications
5
133
2
Order By: Relevance
“…6 Similarly, a systematic review of the structures and processes of care in nursing homes and other residential long-term settings found that residents who were in special care units in assisted living experienced more functional decline than those who were not. 7 To date, most of what is known about assisted living, and more specifically about residents with dementia in assisted living, has been obtained from studies involving a limited number of residences or using state 8 or multistate 9 samples instead of national samples. This study used national data, which recently became available, to describe the proportions and characteristics of assisted living residents with mild, moderate, and severe cognitive impairment; the characteristics of the residences in which they live; and the residences' dementia-related staffing and training, policies, and practices and costs for care.…”
mentioning
confidence: 99%
“…6 Similarly, a systematic review of the structures and processes of care in nursing homes and other residential long-term settings found that residents who were in special care units in assisted living experienced more functional decline than those who were not. 7 To date, most of what is known about assisted living, and more specifically about residents with dementia in assisted living, has been obtained from studies involving a limited number of residences or using state 8 or multistate 9 samples instead of national samples. This study used national data, which recently became available, to describe the proportions and characteristics of assisted living residents with mild, moderate, and severe cognitive impairment; the characteristics of the residences in which they live; and the residences' dementia-related staffing and training, policies, and practices and costs for care.…”
mentioning
confidence: 99%
“…Recent reports indicate that as many as 68% of AL residents have dementia, another 10% have cognitive impairments that are not classifiable as dementia, and 25% have other active psychiatric disturbances such as anxiety and depressive disorders (Rosenblatt et al, 2004). Behavioral and psychological symptoms that occur in 90% of older adults with dementia at some point during the course of their illness (Haupt, Kurz, & Janner, 2000) are reported to occur in more than half of AL residents .…”
mentioning
confidence: 99%
“…Because confusion, difficulty managing medications, and the need for help with basic and instrumental activities of daily living are key reasons for moving to assisted living, one can assume that dementia is somewhat more prevalent in assisted living than in the general population of the same age. We were therefore not surprised with the results of four recent studies, as shown in Table 1 ( ALFA, 2006;Rosenblatt et al, 2004;Sloane, Zimmerman, & Ory, 2001) that reported dementia prevalence in assisted living ranging from approximately 40% to 67%. These prevalence numbers aggregated assisted living residents living both in special units or buildings and those mixed in the general dementia population.…”
Section: Resident Characteristicsmentioning
confidence: 73%
“…Consequently, some of the health-care-related issues for the dementia population in this setting include security of medication storage for all residents; the management of as-needed medications, especially psychotropics (Rosenblatt et al, 2004); and the management of diabetes treatment. Medication undertreatment of medical conditions, such as congestive heart failure and osteoporosis, appears to be prevalent in RC/AL facilities .…”
Section: Health Care Provisionmentioning
confidence: 99%